Resveratrol Alleviating the Ovarian Function Under Oxidative Stress by Alternating Microbiota Related Tryptophan-Kynurenine Pathway - Wang, Jianping; Jia, Ru; Celi, Pietro; Zhuo, Yong; Ding, Xuemei; Zeng, Qiufeng; Bai, Shiping; Xu, Shengyu; Yin, Huadong; Lv, Li; Zhang, Keying (Frontiers in Immunology, 2022)
Oxidative stress (OS) is a key factor regulating the systemic pathophysiological effects and one of the fundamental mechanisms associated with aging and fertility deterioration. Previous studies revealed that resveratrol (RV) exhibits a preventive effect against oxidative stress in the ovary. However, it remains unknown whether gut microbiota respond to resveratrol during an OS challenge. In Exp. 1, layers received intraperitoneal injection of tert-butyl hydroperoxide (tBHP) (0 or 800 μmol/kg BW) or received resveratrol diets (0 or 600 mg/kg) for 28 days. In Exp. 2, the role of intestinal microbiota on the effects of resveratrol on tBHP-induced oxidative stress was assessed through fecal microbiota transplantation (FMT). The OS challenge reduced the egg-laying rate and exhibited lower pre-hierarchical follicles and higher atretic follicles. Oral RV supplementation ameliorated the egg-laying rate reduction and gut microbiota dysbiosis. RV also reversed the tryptphan-kynurenine pathway, upregulated nuclear factor E2-related factor 2 (Nrf2) and silent information regulator 1(SIRT1) levels, and decreased the expression of forkhead box O1 (FoxO1) and P53. These findings indicated that the intestinal microbiota-related tryptophan-kynurenine pathway is involved in the resveratrol-induced amelioration of ovary oxidative stress induced by tBHP in the layer model, while SIRT1-P53/FoxO1 and Nrf2-ARE signaling pathway were involved in this process.